"We are white" : oral tradition, documented history and molecular biology of Xhosa clans descended from non-African forebears and their expression of this ancestry through the idiom of ancestor religion - Hayward, Janet M (Rhodes University, Faculty of Humanities, Department of Anthropology, 2018)
Xhosa clan membership is symbolised by a clan-name (isiduko) and passed along the male line from father to son. This social indicator has a biological counterpart in Y chromosome DNA that passes through successive generations in the patriline. Both relate specifically to a distant patrilineal forebear or apical ancestor. The present study has involved the collection and documentation of oral-historical information relating to the descent of certain Cape Nguni clans from non-African forebears and (where possible) a review of documented accounts of such origins. The research has also included collection of buccal cells from male research participants and analysis of their Y chromosome DNA. This method indicates whether a man's patrilineal forebear lived in Africa. Otherwise, it indicates the broad geographical region from which he originated, hence providing an additional, independent source of information relating to ancestry that can confirm or challenge claims made based on oral history. Ethnographic research into the performance of distinctive ancestor rituals by clan members explores the continuing relevance of foreign ancestry in the contemporary context of rural communities in the Eastern Cape, South Africa. The study heeds calls for the decolonisation of scholarship in various ways: methodologically, through transdisciplinary research; ontologically, by questioning the utility of the nature: culture and related dichotomies; and epistemologically, because instead of relying entirely on the western academic tradition, it takes account of other modes of knowledge production. In rejection of the notion that only one side of history is true, it records multiple voices "“ those of the powerful but also the ordinary. The study deals with race and racial identification, but confirms the superficiality of these constructed differences by offering evidence of their submergence in the unifying power of kinship and descent.
Keywords: Clans -- South Africa -- Eastern Cape; Patrilineal kinship -- South Africa -- Eastern Cape; Xhosa (African people) -- Genealogy; Oral history -- South Africa -- Eastern Cape; Genetic genealogy; Xhosa (African people) -- Rites and ceremonies; Xhosa (African people) -- Race identity